PENGARUH KUNJUNGAN WISATAAN DAN PENERAPAN PROTOKOL KESEHATAN WISATAWAN UJONG BLANG TERHADAP PENDAPATAN PEDAGANG DI MASA PANDEMI COVID-19 - Hikmah Letia; Sufi Sufi (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
This study aims to determine the effect of visiting and implementing the health protocol of Ujong Blang tourists on the income of traders during the COVID-19 pandemic. The data used in this study is primary data obtained by distributing questionnaires to 48 cottage actors who sell around Pante Ujong Blang. The data analysis method used is multiple linear regression analysis with the help of the SPSS version 25 program. The results show that the tourist visit variable (X1) has a positive and significant effect, so that it affects the income of traders (Y) and the variable of implementing health protocols(X2) has a negative and not insignificant effect,so it has no effect on the income of traders (Y). Meanwhile, the results of simultaneous testing show that tourist visits and the application of health protocols have an effect on traders' opinions during the COVID-19 pandemi. Keywords: Tourist Visits, Implementation of Health Protocols, Merchant Income